Fine-root system development and susceptibility to pathogen colonization - Emmett, Bryan; Nelson, Eric B; Kessler, Andre; Bauerle, Taryn L (Planta, 2014)
Root development may exert control on plant–pathogen interactions with soil-borne pathogens by shaping the spatial and temporal availability of susceptible tissues and in turn the impact of pathogen colonization on root function. To evaluate the relationship between root development and resistance to apple replant disease (ARD) pathogens, pathogen abundance was compared across root branching orders in a bioassay with two rootstock genotypes, M.26 (highly susceptible) and CG.210 (less susceptible). Root growth, anatomical development and secondary metabolite production were evaluated as tissue resistance mechanisms. ARD pathogens primarily colonized first and second order roots, which corresponded with cortical tissue senescence and loss in second and third order roots. Defense compounds were differentially allocated across root branching orders, while defense induction or stress response was only detected in first order and pioneer roots. Our results suggest disease development is based largely on fine-root tip attrition. In accordance, the less susceptible rootstock supported lower ARD pathogen abundance and altered defense compound production in first order and pioneer roots and maintained higher rates of root growth in both the ARD soil and pasteurized control compared to the more susceptible. Thus, this rootstock’s ability to maintain shoot growth in replant soil may be attributable to relative replant pathogen resistance in distal root branches as well as tolerance of infection based on rates of root growth.